2018
DOI: 10.4315/0362-028x.jfp-17-335
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Food Sanitizers on Formation of Viable but Nonculturable Salmonella enterica in Poultry

Abstract: A method for microscopic enumeration of viable Salmonella enterica in meat samples was developed by using the LIVE/DEAD BacLight kit technology. A two-step centrifugation and wash process was developed to clean the samples from food and chemical impurities that might otherwise interfere with the appropriate staining reactions. The accuracy of the BacLight kit-based viability assessments was confirmed with various validation tests that were conducted by following the manufacturer's instructions. For the biocide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The included studies are located in references (1,2,10,11,12,14,20,24,26,30,31,32,36,37,39,40,41,43,44,46,48,50,56,60,61,62). The publication date ranged from 2004 to 2020, but most of the articles were published from 2013 onwards.…”
Section: Review Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies are located in references (1,2,10,11,12,14,20,24,26,30,31,32,36,37,39,40,41,43,44,46,48,50,56,60,61,62). The publication date ranged from 2004 to 2020, but most of the articles were published from 2013 onwards.…”
Section: Review Methodologymentioning
confidence: 99%
“…Peroxyacetic acid (PAA), also known as peracetic acid or peroxyacids, is a mixture of peroxyacetic acid, octanoic acid, acetic acid, hydrogen peroxide, peroxyoctanoic acid, and 1hydroxyethylidene-1,1-diphosphonic acid (53) (53). PAA can be purchased from several chemical suppliers around the world, either as a laboratory grade chemical or as a commercial formulation with specific instructions for use in poultry applications (17,26,39,47,63). PAA should be stored in a well-ventilated place, in tightly closed containers that are protected from sunlight and kept away from other materials (17,63).…”
Section: Highlightsmentioning
confidence: 99%
“…Most non-viable cell groups contained more than 0.7% v/v acetate, indicating that high-level acidity environmental condition induced cell death rather than the formation of a VBNC state, although a previous study had reported that an S. enterica VBNC state could be induced by lactic acid or peracetic acid (Purevdorj-Gage et al, 2018). Interestingly, a VBNC state was induced under 0.7% v/v acetate by supplying sufficient nutrients (100%), suggesting that nutrients were essential for S. enterica entering a VBNC state in response to multistress conditions including inorganic salts and weak acid.…”
Section: Salmonella Enterica Vbnc State Formationmentioning
confidence: 87%
“…In addition to the natural environment, the generation of an S. enterica VBNC state also occurred during chlorination of wastewater or food (Oliver et al, 2005;Highmore et al, 2018). In the food industrial environment, the common non-ionic detergents and sanitizers were found to induce an S. enterica VBNC state formation (Morishige et al, 2013;Purevdorj-Gage et al, 2018;Robben et al, 2018). Besides, oxidation stress induced by non-thermal sterilization technologies had been confirmed to have a positive relationship with generation of VBNC S. typhimurium cells (Liao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The generation of S. enterica VBNC state occurs during the chlorination of wastewater or food ( Oliver et al, 2005 ; Zeng et al, 2013 ). Non-ionic detergents and sanitizers can also induce S. enterica into VBNC state ( Morishige et al, 2013 ; Purevdorj-Gage et al, 2018 ; Robben et al, 2018 ). Furthermore, a multi-stress environment in complex components of food and storage conditions may induce the VBNC state formation of foodborne pathogens ( Lin et al, 2016 ; Miao et al, 2016 ; Xu et al, 2016a,b ).…”
Section: Discussionmentioning
confidence: 99%